“The world is dry, but I am fine” Self-perception of the human right to water and sanitation in trainee teachers - Lázaro-Salazar, Ana Sofía; Guerra-Ramos, María Teresa; Fargher-Navarro, Lane Frederick; Hoogesteijn-Reul, Almira Lydia (Frontiers in Education, 2025)
The water in Mexico does not meet the standards outlined by the United Nations General Assembly in the document “Human Right to Drinking Water and Sanitation” (HRWS). This pertains to potability, acceptability, sufficiency, accessibility, and affordability. An analysis was conducted on the public drinking water service and its impact on the socio-ecological well-being of students attending teacher training schools in Yucatán, Mexico. Online workshops were held using a competency-based methodology. Questionnaires were developed to gather information on the state of public drinking water and sewage services (n = 200) to evaluate participants’ experiences with public water management. Participants completed a questionnaire assessing their understanding and perception of the HRWS (n = 200) and a self-assessment questionnaire (n = 200). Findings indicate that 84% acknowledged governance issues in access to water and its quality (questionnaires), while only 11% of students rated their HRWS as poor to very poor (self-assessment). This cognitive dissonance arises from the gap between knowledge about the water service and self-perception. It suggests that the system’s inadequacies have become normalized, affecting individuals’ willingness to engage in pro-environmental actions and behaviors. The students recognize a water crisis and believe that polluting practices must be addressed. They also feel that increasing public involvement in water management through awareness is essential. However, they do not see themselves as affected by the crisis or as agents of change through their future roles as teachers.